منهج تعليم اللغة العربية لتلاميذ مدرسة المعاقين سمعيا بالرقيبة دراسة وصفية تحليلية - صالحي, قريشي, سعدية حسناء (University of El-oued, 2021)
إن إصابة أي عضو من أعضاء النطق يحدث خلل في عملية التعليم والتعلم. عنوان الدراسة: منهج تعليم اللغة العربية لتلاميذ مدرسة المعاقين سمعيا بالرقيبة دراسة وصفية تحليلية. جاء هذا البحث في فصول: الفصل الأول: مناهج التعليم العام الفصل الثاني: الإعاقة السمعية الفصل الثالث: إجراءات الدراسة الميدانية من أهم النتائج التي توصلت إليها الباحثات: أن المنهج التعليمي للمعاقين سمعياً يقوم على عدة مبادئ تجعل التحصيل الأكاديمي لهذه الفئة سهل وفي متناول الجميع. Summary: The infliction of one the vocalization organs makes foult in education and learning process. Study ti the: Method of Arabic lonuage educahion for ourally hindering pupihs in Reguiba school: Analytical de scriptive study. Research part: Fsxst part: Methode of General Education Second part: Aually hindering Third part: Measures of Thes most important result: which the researchers get it that the educational method for ourally hindering pupils depends on mony principles that makes the academic collecting for this category very simple and reachable.
Keywords: مدرسة المعاقين منهج التعلم